2018
DOI: 10.15421/011802
|View full text |Cite
|
Sign up to set email alerts
|

Prediction of sweet corn yield depending on cultivation technology parameters by using linear regression and artificial neural network methods

Abstract: Artificial neural networks and linear regression are widely used in particularly all branches of science for modeling and prediction. Linear regression is an old data processing tool, and artificial neural networks are a comparatively new one. The goal of the study was to determine whether artificial neural networks are more accurate than linear regression in sweet corn yield prediction. In the study we used a dataset obtained from field experiments on the technological improvement of sweet corn cultivation. T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 42 publications
0
6
0
Order By: Relevance
“…The results of the study proved that neural network models provide considerably better accuracy of predictions [Kaul et al 2005;Choubin et al 2016;Lykhovyd 2018]. Besides, these models can operate with non-numeric information that is very helpful in some cases.…”
Section: Discussionmentioning
confidence: 81%
“…The results of the study proved that neural network models provide considerably better accuracy of predictions [Kaul et al 2005;Choubin et al 2016;Lykhovyd 2018]. Besides, these models can operate with non-numeric information that is very helpful in some cases.…”
Section: Discussionmentioning
confidence: 81%
“…Moreover, the distribution of the errors presents a normal curve. Hence, it can be concluded that the error of the ANN model was systematic error and they were not biased (Lykhovyd, 2018).…”
Section: Resultsmentioning
confidence: 99%
“…Moreover, the model is adaptive to different inputs via its learning process, which make it powerful for dealing with complex problems in practice (Shanmuganathan, 2016). Moreover, the ANN was widely used in cereal kernel studies and illustrated to have a satisfying performance in prediction problems (Khazaei, Shahbazi, Massah, Nikravesh, & Kianmehr, 2008; Lykhovyd, 2018; Zhou, Kimbeng, Tew, Gravois, & Pontif, 2011). In this research, there were numerous predictors and the relationship between mechanical properties and BR was not clarified by previous studies.…”
Section: Methodsmentioning
confidence: 99%
“…Triplicates were made and their statistical texture values along with the area of the aggregates were loaded as the training data for the neural network with a 6–1 architecture. Neural networking was performed by NeuroXL Predictor, a neural network-based add-in for Microsoft Excel developed by OLSOFT and is capable of advanced data forecasting, classification and clustering [ 46 , 47 ]. The trained neural network was then tested with the data from a new set of Lys samples of pre-determined concentrations.…”
Section: Methodsmentioning
confidence: 99%